Erratum (Current Neuropharmacology, 2007)
Due to an overlook on the author's side, some of the references in the legends of figures of an article L-Glutamate and its ionotropic receptor in the nervous system of cephalopods” by A. Di Cosmo, C. Di Cristo and J. B. Messenger, published in the journal Current Neuropharmacology Volume 4, issue 4, October 2006, were wrong. The complete list of correct references is as follows: Figure 1 Reference 49 Figure 2 Reference 16 Figure 3 Reference 21 Figure 5 Reference 12 Figure 6 Reference 33 Figure 7 Reference 33 Figure 8 Reference 25